2013
DOI: 10.1002/anie.201300907
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Application of β‐Substituted Pauson–Khand Adducts: Trifluoromethyl as a Removable Steering Group

Abstract: Against the rules: The synthesis of the previously unknown β‐substituted regioisomers of the intermolecular Pauson–Khand reaction of terminal alkynes is reported. This regiochemistry was achieved by using the trifluoromethyl group as a removable directing group on the alkyne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…In a later study [ 72 ], Riera and Fustero generalized the use of trifluoromethylalkynes as substrates for the PKR. The copper-catalyzed trifluoromethylation of terminal alkynes described by Qing and co-workers [ 73 ] allowed the efficient preparation of a small library of substrates bearing aryl, alkyl, and alkenyl substitutents.…”
Section: Reviewmentioning
confidence: 99%
“…In a later study [ 72 ], Riera and Fustero generalized the use of trifluoromethylalkynes as substrates for the PKR. The copper-catalyzed trifluoromethylation of terminal alkynes described by Qing and co-workers [ 73 ] allowed the efficient preparation of a small library of substrates bearing aryl, alkyl, and alkenyl substitutents.…”
Section: Reviewmentioning
confidence: 99%
“…Regioselectivity in other intermolecular [2+2+1] reactions such as the Pauson-Khand reaction is often difficult to achieve in the absence of clear stereoelectronic differentiation of alkyne substituents, and remains a siginficant synthetic challenge. [10] In an effort to design more useful and practical pyrrole syntheses, we have explored several routes to the chemo- and regioselective heterocoupling of alkynes in the [2+2+1] reaction to yield highly substituted pyrroles. Herein, we report that silyl-protected alkynes serve as excellent heterocoupling partners, yielding pentasubstituted N-aryl pyrroles in high chemo- and regioselectivity (Figure 1, bottom).…”
mentioning
confidence: 99%
“…28 More recently, the Riera group demonstrated the utility of trifluoromethyl as a removable steering group that can be released from -substituted Pauson-Khand products by treatment with DBU in nitromethane/H 2 O. 29 Furthermore, Reira reported that ethylene glycol as an additive can significantly accelerate intermolecular Pauson-Khand reactions, doubling the yields, even for challenging combinations such as cyclopentene/(trimethylsilyl)acetylene or cyclopentene/N-Boc-propargylamine. 30 In an earlier work, we found that chlorinated solvents such as CH 2 Cl 2 could be replaced by either an ionic liquid such as 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim]PF 6 ) or a two-phase system such as [bmim]PF 6 /methylcyclohexane (MCH) in intermolecular Co 2 (CO) 8 -mediated Pauson-Khand reactions in the presence of NMO at room temperature with good yields and regioselectivities for bicyclic alkenes, such as norbornene (26) (Scheme 3).…”
Section: Syn Lettmentioning
confidence: 99%